Toxicity of some pesticides and oil plant extracts to plant sucking pests - EI-Khodary, A. S.; Samy, M. A.; Keratum, A. Y.; EI-Fakharany, S. K. M. (2007)
Toxicity of certain compounds including pesticides (fenitrothion and etoxazole), mineral oil (KZ-oil)
Includes references.
Summary in Arabic.
1
Keywords: Vegetables -- Diseases and pests -- Control; Fruits; Oil plants; Plant extracts; sucking